A Phenotypic Screen Identifies Cyclic Peptide Compounds that Induce Repeat Expansion in Yeast. - Economos, Nicholas G. (Tufts Archival Research Center, 2005)
Expansion of repeat sequences in the eukaryotic genome can result in dangerous consequences often implicated in the pathology of severe human diseases. Out-of-context telomeric extension in immortalized cancer cell lines and expanded GAA repeat tracts in sufferers of the disease Friedreich's ataxia are two such examples. The mechanisms related to repeat expansion have been widely investigated, but are poorly understood and likely complex. To identify small molecules that may induce repeat expansion and to further understand these mechanisms, we developed a phenotypic screening system to identify small cyclic peptides that induce the expansion of tandem repeat sequences modeled in yeast (Saccharomyces cerevisiae) using a large intracellularly constructed cyclic peptide library. This paper presents the isolation and characterization of three cyclic peptides that demonstrate inverted human telomeric repeat expansion activity after screening an initial pool of 125,000 transformants. Further analyses reveal that all three of the isolated peptides additionally induce expansion in GAA repeats modeled in a similar system. This work showcases the efficient ability of our screening system to identify agents with repeat expanding properties and highlights three interesting molecules that induce instability in at least two different repeat sequences.